Kuresif 2.0 Barcode Technology to Improve Maternal Knowledge and Attitudes Regarding Complementary Feeding - Ratna Suminar; Henri Setiawan; Fatmawati Karim; Widya Maya Ningrum (Inspirasi Foundation, 2024)
Objective: This study aims to evaluate the effectiveness of Kuresif 2.0: Barcode in enhancing mothers’ knowledge and attitudes regarding complementary feeding rich in animal protein. Method: A quasi-experimental design was employed, utilizing a pretest-posttest control group framework. The sample consisted of 100 mothers of toddlers, divided into 50 in the control group and 50 in the intervention group, selected through total sampling. Statistical analysis was performed using the Wilcoxon Test and Cohen’s d for effect size. A questionnaire served as the research instrument. Results: The findings indicate that Kuresif 2.0: Barcode significantly improved mothers’ knowledge and attitudes regarding complementary feeding rich in animal protein. The knowledge variable exhibited a t-value of -17.955, with a p-value less than 0.001, indicating a highly significant increase in knowledge. Cohen’s effect size for knowledge was calculated at 0.7, suggesting a moderate impact of the intervention. For attitudes, the t-value was -19.298, also with a p-value less than 0.001, confirming a significant influence of the intervention. The effect size for attitudes, represented by Cohen’s d, was 0.4, indicating a small to moderate effect of the intervention on maternal attitudes. Conclusion: Kuresif 2.0: Barcode significantly enhanced mothers’ knowledge, demonstrating a stronger effect than on attitudes. These results underscore the importance of implementing structured interventions to foster improved knowledge and attitudes among mothers related to complementary feeding practices.